Hydrogen reduction studies of low-grade multimetallic magnetite ore pellets - Mishra B.; Kumar Singh A.; Shankar Mahobia G. (My University, 2025)
The hydrogen reducibility of pellets made from a low-grade multimetallic magnetite ore (Fe content ∼ 45 %) was investigated in the present study. Pellets were reduced in a horizontal tube furnace at temperatures ranging from 973 K to 1173 K for 1 to 60 min. Pure Hydrogen (H2) gas (99.9 %) at three flow rates of 0.25 L/min, 0.5 L/min, and 1 L/min were blown during the reduction process. A maximum reduction degree of 94.07 %, metallization ratio of 0.925, and H2 gas utilization of 9.01 % were obtained at a temperature and a reduction time of 1173 K and 60 min, respectively. In order to optimize the hydrogen utilization, a reduction temperature of 1173 K, a reduction time of 45 min, and a gas flow rate of 0.25 L/min were selected, resulting in a reduction degree and metallization ratio of 90 % and 0.89, respectively. The cold crushing strength (CCS) of the reduced pellets initially decreased and then increased slightly, exhibiting behavior similar to high-grade ores. Imputities like SiO2, Al2O3, and MgO, present in the low grade ores are found to control the porosity of the pellets, directly affecting the CCS and reducibility of the pellets. © 2024 Elsevier Ltd